2019
DOI: 10.3390/s19081749
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis for Surface Acoustic Wave Device Characteristic Properties and Sensitivity

Abstract: The most vital step in the development of novel and existing surface acoustic wave (SAW)-based sensors and transducers is their design and optimization. Demand for SAW devices has been steadily increasing due to their low cost, portability, and versatility in electronics, telecommunications, and biosensor applications. However, a full characterization of surface acoustic wave biosensors in a three-dimensional (3D) finite element model has not yet been developed. In this study, a novel approach is developed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Analyses based on the coupled mode (COM) theory [31,32] have helped us to greatly improve our knowledge of the role of mass, temperature, and materials in SAW sensors; however, to obtain the parameters of COM, either measurement or borrowing from some related theoretical modeling such as FEA is required [33]. In the latter case, it takes a superfluous action, since FEA has already provided a way for models to quickly and easily check results as well as showing significant benefits to geometry, material, and physical field configurations [34,35]. Hence, in this research, the FEA approach was used to investigate the torque sensing mode and the effects resulting from crystal cut and wave-guide layer material and thickness.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses based on the coupled mode (COM) theory [31,32] have helped us to greatly improve our knowledge of the role of mass, temperature, and materials in SAW sensors; however, to obtain the parameters of COM, either measurement or borrowing from some related theoretical modeling such as FEA is required [33]. In the latter case, it takes a superfluous action, since FEA has already provided a way for models to quickly and easily check results as well as showing significant benefits to geometry, material, and physical field configurations [34,35]. Hence, in this research, the FEA approach was used to investigate the torque sensing mode and the effects resulting from crystal cut and wave-guide layer material and thickness.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Instead of using a full model, a simplified 3D geometry was built to run the simulations for the sake of avoiding large memory cost and time consumption. FEA through COMSOL Multiphysics ® [25,34,35] was adopted in this research to facilitate computational modeling of the SH-SAW when different cut angles, wave-guide layer materials and thicknesses, and torques are involved. The piezoelectric constitutive equation [36] to be solved is expressed in Equation (3), which couples the mechanical effect as governed by Newton’s law and the electrical effect as determined by Gauss’s law:leftTij=cijklSklekijEkDi=eijkSjk+εijEj, where T ij is the stress matrix, S jk is the strain matrix, E k is the applied electric field, and D i is the electric displacement vector.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…To overcome these challenges, an optimized surface acoustic wave (SAW)-based multiple-layer sensor and passive electrode potential sensor was integrated with microfluidic 96-well plates and fabricated by traditional microfabrication techniques. Full optimization of the sensor settings and the flow rate was conducted by finite element analysis to increase the sensitivity and generate appropriate shear stress on cells [63][64][65][66]. It was found that a fiber inspired smart scaffold (FiSS) platform established in the Mohapatra laboratory allows for the growth of 3D tumor-like aggregates (tumoroids), which resemble in vivo tumors [67].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…However, these methods are very complex and are mainly used in telecommunication applications such as filters and resonators. To overcome these limitations, Finite Element Method (FEM) simulation was investigated and has proven to be the most suitable method for metrological characterization of SAW devices prior to their fabrication in a clean room [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%